Characteristics of choice and satisfaction regarding the use of ultraviolet blockers in the golf population in Republic of Korea: A quantitative study - Choi, Jiahn; Kwon, Ki Han (Health science reports, 2023)
Background and AimsKorea's golf population surpassed 5 million (5.15 million) as of 2020 according to data analyzed by Shinhan Financial Investment in 2021. Due to the continuous increase in the golf population, it is necessary to study the use of specific sunscreens. Men and women are using sunscreen selective attributes based on the actual use and perception of sunscreens for life. A questionnaire survey was conducted for an analysis of the effect of product satisfaction.MethodsStatistical processing of materials collected by the data analysis method is analyzed using the Statistical Package for Social Science WIN 25.0 statistical package program through the process of data coding and data cleaning.ResultsThis exercise was done under 3–4 h of strong ultraviolet (UV) rays, so products that have ensured the durability of UV protection are needed. Among the demographic characteristics of the golf population, gender, age, academic background, occupation, marriage status, and monthly income were investigated, and it was confirmed that the information path of a particular product was affected by the choice of purchase, increasing satisfaction and repurchase.ConclusionAn analysis of the paper's survey showed that men's awareness and interest in sunscreens increased. It is expected that differentiated strategies will be needed for products that match the actual conditions and aptitudes of the effective golf population.